Suitability of the isolated chicken eye test for classification of extreme pH detergents and cleaning products. Issue 3 (April 2015) - Cazelle, Elodie; Eskes, Chantra; Hermann, Martina; Jones, Penny; McNamee, Pauline; Prinsen, Menk; Taylor, Hannah; Wijnands, Marcel V.W.
Highlights Suitability of ICE to identify GHS Cat. 1 extreme pH detergent and cleaning formulations. Overall predictivity of ICE to identify GHS Cat. 1 detergent and cleaning formulations. Comparison between in vitro versus non-testing approaches for hazard classification.